Spillovers Through Banking Centers : A Panel Data Analysis. (IMF Working Papers; Working Paper, 2000)
To test the role of bank lending in transmitting currency crisis we examine a panel of BIS data on bank flows to 30 emerging markets disaggregated by 11 banking centers. We find that bank exposures to a crisis country help predict bank flows in third countries after the Mexican and Asian crisis, but not after the Russian crisis. In the latter, there is evidence of a generalized outflow from emerging markets, rather than outflows linked to prior exposure to Russia.